Prevalence, severity, and risk indicators of gingival inflammation in a multi-center study on South American adults: a cross sectional study (Journal of Applied Oral Science, 2016)
Objectives: The aim of this study is to investigate the prevalence and severity of gingival inflammation and associated risk indicators in South American adults. Material and Methods: Multi-stage samples totaling 1,650 adults from Porto Alegre (Brazil), Tucumán (Argentina), and Santiago (Chile) were assessed. The sampling procedure consisted of a 4-stage process. Examinations were performed in mobile dental units by calibrated examiners. A multivariable logistic regression model was utilized for associating variables as indicators of gingival inflammation (GI) (Gingival Index ≥0.5). Statistical significance was set at 0.05. Results: A total of 96.5% of the adults have GI. Regarding the severity of GI, 22.5% of participants examined have mild GI, 74.0% have moderate GI, and 3.6% have severe GI. The multivariate analyses identify the main risk indicators for GI as adults with higher mean of Calculus Index (OR=18.59); with a Visible Plaque Index ≥30% (OR=14.56); living in Santiago (OR=7.17); having ≤12 years of schooling (OR=2.18), and females (OR=1.93). Conclusions: This study shows a high prevalence and severity of gingival inflammation, being the first one performed in adult populations in three cities of South America.